Malignant syphilisand neurosyphilisin aids patient - Martinelli, Fabio Leoncio B.; Bedaque, Eleni Aparecida; Macedo, Audrey E.; Santos, Alessandra S.P.; Miranda, Paula P.T. de; Curti Júnior, Renato (Brazilian Journal of Sexually Transmitted Diseases, 2023)
In this report, a 28 year-old woman seropositive for HIV was admitted at the Instituto de Infectologia “Emilio Ribas” with a two months history of bizarre cutaneous lesions, varying from 1 to 5 cm of diameter, in different stages of evolution. During the investigation, serology for syphilis (VDRL) resulted 1/64. Histopathological study of the skin wounds revealed dermal and perivascular infiltration by lymphocytes and plasma cells. Cerebrospinal fluid (CSF) study revealed pleocytosis, increase in protein levels and a negative VDRL test. The treatment with crystalline penicillin resulted in excellent clinical response and regression of skin lesions. CSF obtained after therapy showed resolution. She was discharged and refered for ambulatory follow up. Three months later serum VDRL resulted 1/8 without any kind of recurrence.